Patterns of memory impairment and perseverative behavior discriminate early Alzheimer's disease from subcortical vascular dementia - Traykov, Latchezar; Baudic, Sophie; Raoux, Nadine; Latour, Florence; Rieu, Dorothée; Smagghe, Alain; Rigaud, Anne-Sophie (Journal of the neurological sciences, 2005)
Previous research suggests that the neuropsychological deficits in Alzheimer's disease (AD) are different from that of vascular dementia (VaD), especially with respect to memory, language and executive functions, but negative findings were reported. Our objective was to clarify the cognitive syndrome in AD and VaD in the early stage of these disorders. We investigated 45 patients with early AD, 23 patients with subcortical VaD and 35 normal controls. All subjects were assessed with neuropsychological battery designed to measure memory, language, praxis and executive functions. Patients with AD had significantly worse scores on Story Recall ( p<0.02) and on all measures of the Free and Cued Selective Reminding Test ( p<0.03 to 0.001) than did patients with VaD, as well as greater number of perseverations ( p<0.02) on category fluency. Conversely, VaD patients had more perseverations ( p<0.02) on the Modified Card Sorting Test. Despite the similar degree of overall cognitive deterioration, the findings show more impaired retrieval from long-term storage in AD than in VaD. Moreover, the data suggest that AD and subcortical VaD affect perseverative behavior in a different fashion. These results may be helpful in differentiating AD from VaD in the early stage of these disorders, when mental impairments are not pervasive yet.